How public health services pay for radiotherapy in Europe: an ESTRO–HERO analysis of reimbursement. Issue 1 (January 2020) - Lievens, Yolande; Defourny, Noémie; Corral, Julieta; Gasparotto, Chiara; Grau, Cai; Borras, Josep Maria; ,
Summary: Reimbursement is a key factor in defining which resources are made available to ensure quality, efficiency, availability, and access to specific health-care interventions. This Policy Review assesses publicly funded radiotherapy reimbursement systems in Europe. We did a survey of the national societies of radiation oncology in Europe, focusing on the general features and global structure of the reimbursement system, the coverage scope, and level for typical indications. The annual expenditure covering radiotherapy in each country was also collected. Most countries have a predominantly budgetary-based system. Variability was the major finding, both in the components of the treatment considered for reimbursement, and in the fees paid for specific treatment techniques, fractionations, and indications. Annual expenses for radiotherapy, including capital investment, available in 12 countries, represented between 4·3% and 12·3% (average 7·8%) of the cancer care budget. Although an essential pillar in multidisciplinary oncology, radiotherapy is an inexpensive modality with a modest contribution to total cancer care costs. Scientific societies and policy makers across Europe need to discuss new strategies for reimbursement, combining flexibility with incentives to improve productivity and quality, allowing radiation oncology services to follow evolving evidence.